2016
DOI: 10.1093/mnras/stw878
|View full text |Cite
|
Sign up to set email alerts
|

Long-term X-ray spectral variability in AGN from the Palomar sample observed bySwift

Abstract: We present X-ray spectral variability of 24 local active galactic nuclei (AGN) from the Palomar sample of nearby galaxies, as observed mainly by Swift. From hardness ratio measurements, we find that 18 AGN with low accretion rates show hardening with increasing count rate, converse to the softer-when-brighter behaviour normally observed in AGN with higher accretion rates. Two AGN show softening with increasing count rate, two show more complex behaviour, and two do not show any simple relationship.Sufficient d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 112 publications
11
53
1
Order By: Relevance
“…β does not depend on λ E either for −2 λ E 0, while it shows a weak trend toward smaller absolute values for λ E −2, suggesting a possible agreement with Connolly et al (2016). In fact, according to their work, there might be a transition to harder when brighter trend (β > 0) for very low Eddington ratio sources.…”
Section: Black-hole Mass and Eddington Ratiomentioning
confidence: 64%
See 2 more Smart Citations
“…β does not depend on λ E either for −2 λ E 0, while it shows a weak trend toward smaller absolute values for λ E −2, suggesting a possible agreement with Connolly et al (2016). In fact, according to their work, there might be a transition to harder when brighter trend (β > 0) for very low Eddington ratio sources.…”
Section: Black-hole Mass and Eddington Ratiomentioning
confidence: 64%
“…8, There is no clear trend for λ E −2. Even though the number of points for the first bin is scarce, the absolute value of β for very low Eddington ratio λ E −2 is smaller, suggesting that for even lower Eddington ratios it might become positive, transitioning to harder when brighter trend as found by Connolly et al (2016). Bottom: histogram of Eddington ratio is also shown.…”
Section: Black-hole Mass and Eddington Ratiomentioning
confidence: 93%
See 1 more Smart Citation
“…The counts of our sources in each epoch (median ∼350) generally cannot constrain Γ effectively; e.g., Brightman et al (2013) found that even a simple powerlaw model would require 1000 counts to obtain an uncertainty (90% confidence level) of Γ within 0.2. Studies of quasars and local luminous AGNs show that spectral variability generally follows a "softer when brighter" behavior (e.g., Sobolewska & Papadakis 2009;Gibson & Brandt 2012;Sarma et al 2015;Connolly et al 2016). 22 However, based on the empirical X-ray flux-Γ relations given by those studies, the Γ variability amplitudes for our sources are expected to be small and not detectable given the counts we have in each epoch.…”
Section: Spectral Variability 321 Methodsmentioning
confidence: 83%
“…The spectra of most Seyfert galaxies with Eddington ratios above 0.01 typically become steeper in their brighter phases (e.g., Markowitz et al, 2003;Sobolewska and Papadakis, 2009;Connolly et al, 2016), as well as for many galactic black hole binary systems (e.g., Remillard and McClintock, 2006;Done et al, 2007;Dong et al, 2014). This is known as "softer when brighter" behavior and translates to a negative β value according to Equation 2.…”
Section: Spectral Variabilitymentioning
confidence: 99%